Recovery of deteriorated upland rice seeds through ultra-low magnetic field exposure and its effects on germination and enzyme activity - DWIJOWATI ASIH SAPUTRI; ROCHMAH AGUSTRINA; BAMBANG IRAWAN; YUSNITA YUSNITA (Asian Journal of Agriculture, 2026)
Abstract. Saputri DA, Agustrina R, Irawan B, Yusnita. 2026. Recovery of deteriorated upland rice seeds through ultra-low magnetic field exposure and its effects on germination and enzyme activity. Asian J Agric 10 (1): g100138. https://doi.org/10.13057/asianjagric/g100138. Aged upland rice (Oryza sativa L. var. Lumbung Sewu Cantik, LSC) seeds often exhibit reduced germination capacity and metabolic activity due to prolonged storage. Pretreatment with a low-intensity static magnetic field (magnetopriming) demonstrated the potential to revitalize and improve the quality of aged seeds. This study examined the effect of a low-intensity static magnetic field (magnetopriming) at 0.2 mT on the germination performance and enzyme activity of 10-month-old LSC seeds. Seeds were exposed to the magnetic field at different exposure durations, with untreated seeds as controls. Several germination indices and enzyme activities were evaluated. The results showed significant improvement in Final Germination Percentage (FGP) at optimal exposure durations, with no substantial changes were observed in Mean Germination Time (MGT), First Day Germination (FDG), Last Day of Germination (LDG), Coefficient of Velocity of Germination (CVG), Germination Index (GI), Germination Rate Index (GRI), and Time Spread of Germination (TSG). Enzyme assays revealed that α-amylase and protease activities were significantly increased following magnetic field exposure, whereas dehydrogenase activity showed only slight, non-significant enhancement. The study demonstrates that low-intensity magnetic field exposure can serve as an eco-friendly, non-chemical priming method that partially enhances the performance of aged seeds and improves early seedling vigor. Within the scope of this study, the observed improvements in germination and enzyme activity suggest that this non-chemical approach may support more efficient seed utilisation under sub-optimal storage conditions.